Mechanism of Adaptation Of Children Left Without Parental Care To The Foster Family - Dildora Rakhimova (Penerbit Jurnal Indonesia, 2024)
Today, the number of operating family orphanages is 136, where 808 children are being educated. With the initiatives of the President, the activity of these families is aimed at further improvement, as well as a number of comforts and conveniences for parents, their own children and foster children, new laws defining benefits were adopted. This article presents the anylyses of activities in terms of “Family Upbringing” program in order assit the adaptation of children left without parental care in foster families and prepare them for family life.